Розвиток окислювального гетерогенного каталізу в Інституті сорбції та проблем ендоекології НАН України - Zazhigalov, Valeriy O. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2023)
In this publication the results of heterogeneous catalytic processes of different nature compounds oxidation in productive and ecological catalysis obtained in Institute for Sorption and Problems of Endoecology NAS of Ukraine during last 30-years are summarized. The problems of effective catalysts synthesis for these reactions and development of nontraditional preparation methods to catalysts technology are considered. The results obtained in investigation of saturated hydrocarbons (methane, ethane, propane, butane, pentane) partial oxidation in valuable products (formaldehyde, ethylene, propylene, maleic and phthalic anhydrides) are presented. The mechanisms of paraffins hydrocarbons transformation are presented. New approaches to effective catalysts preparation, which based on alternative methods (mechanochemistry, sonochemistry, barothernal synthesis, ionic implantation) using, for these processes are shown and the comparison of results obtained on synthesis catalysts with known literature data was realized. It was established that in most cases the catalysts prepared by us are more effective in different processes that known analogous catalysts. New schemes of maleic anhydride production in excess of n-butane in reaction mixture and phthalic anhydride from n-pentane with two catalysts in catalytuic bed were proposed. The process of ethanol oxidation to acetaldehyde was studied and very effective catalysts for this process realization were proposed. The synthesis of the catalysts for environment protection (total oxidation of H2S, CO and CO in hydrogen excess) is considered and it was shown that the developed catalysts don’t give in activity foreign analogues. The results obtained at catalysts preparation for photocatalytic degradation of different organic compounds, including herbicides and medical substances, in water medium are presented. The positive effects of the catalysts synthesis by nontradional methods (mechanochemistry and sonochemistry) for effective photocatalysts preparation are shown. The new perspective directions of catalytic oxidation processes and methods of the catalysts preparations are presented.